The Ecological Aspects of Urban Structure of Balige District Kabupaten Toba, Indonesia - Rafika Hilmi Nasution (Talenta Publisher, 2021)
Balige is the capital of Toba Samosir Regency. Balige District continues to develop dynamically, marked by the development and changes of the physical city structure Balige. It is about the real implications of a city’s physical growth and development that move dynamically, which can be seen from urban, suburban, and rural land-use patterns. The aim is to determine the ecological aspects of urban structures in the Balige District. The method used in selection is done through secondary data that does not directly provide data to researchers or analyzed documents and concluded. Initially, Balige City was centered on the pier up to Sisingamangaraja’s field, evidenced by water transportation still used today. However, the result of the study showed changes in the pattern of land use due to economic growth and social transformation.